A customized long acting formulation of the kisspeptin analog C6 triggers ovulation in anestrus ewe. (31st March 2022) - Salzano, Giuseppina; Robert, Vincent; Lomet, Didier; Decourt, Caroline; Hommet, Elise; Derouin‐Tochon, Flavie; Hellier, Vincent; Savina, Farah; Vishwanatha, Thimmalapura‐Marulappa; Aucagne, Vincent; Gref, Ruxandra; Beltramo, Massimiliano
Abstract: The modulation of the kisspeptin system holds promise as a treatment for human reproductive disorders and for managing livestock breeding. The design of analogs has overcome some unfavorable properties of the endogenous ligands. However, for applications requiring a prolongation of drug activity, such as ovulation induction in the ewe during the non‐breeding season, additional improvement is required. To this aim, we designed and tested three formulations containing the kisspeptin analog C6. Two were based on polymeric nanoparticles (NP1 and NP2) and the third was based on hydrogels composed of a mixture of cyclodextrin polymers and dextran grafted with alkyl side chains (MD/pCD). Only the MD/pCD formulation prolonged C6 activity, as shown by monitoring luteinizing hormone (LH) plasma concentration (elevation duration 23.4 ± 6.1, 13.7 ± 4.7 and 12.0 ± 2.4 h for MD/pCD, NP1 and NP2, respectively). When compared with the free C6 (15 nmol/ewe), the formulated (MD/pCD) doses of 10, 15 and 30 nmol/ewe, but not the 90 nmol/ewe dose, provided a more gradual release of C6 as shown by an attenuated LH release during the first 6 h post‐treatment. When tested during the non‐breeding season without progestogen priming, only, the formulated 30 nmol/ewe dose triggered ovulation (50% of ewes). Hence, we showed that a formulation with an adapted action time would improve the efficacy of C6 with respect to inducing ovulation during the non‐breeding season. This result suggests that formulations containing a kisspeptin analog might find applications in the management of livestock reproduction but also point to the possibility of their use for the treatment of some human reproductive pathologies.